2017
DOI: 10.4300/jgme-d-16-00817.1
|View full text |Cite
|
Sign up to set email alerts
|

Does the Flipped Classroom Improve Learning in Graduate Medical Education?

Abstract: In this crossover study comparing a single flipped classroom module with a standard lecture, we found mixed statistical results for performance measured by multiple-choice questions. As the differences were small, the flipped classroom and lecture were essentially equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 23 publications
6
63
0
5
Order By: Relevance
“…The flipped curriculum had limited uptake, in terms of residents completing outside reading and faculty and fellows conducting case discussions, yet both groups reported high satisfaction with the new approach. Our study fits well within the current landscape of flipped classroom studies in GME that show mixed objective results 14,15 but positive perceptions of the flipped classroom curriculum overall. [7][8][9]15 This raises the question of whether a flipped classroom methodology works within GME curricula.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The flipped curriculum had limited uptake, in terms of residents completing outside reading and faculty and fellows conducting case discussions, yet both groups reported high satisfaction with the new approach. Our study fits well within the current landscape of flipped classroom studies in GME that show mixed objective results 14,15 but positive perceptions of the flipped classroom curriculum overall. [7][8][9]15 This raises the question of whether a flipped classroom methodology works within GME curricula.…”
Section: Discussionsupporting
confidence: 78%
“…Our study fits well within the current landscape of flipped classroom studies in GME that show mixed objective results 14,15 but positive perceptions of the flipped classroom curriculum overall. [7][8][9]15 This raises the question of whether a flipped classroom methodology works within GME curricula. 16 The flipped classroom is prevalent in GME, as a 2017 survey showed over 83% of IM residency programs use it for at least some of their residency training.…”
Section: Discussionsupporting
confidence: 78%
“…However, concerns have been raised about implementing the flipped classroom in GME . To date, only several small studies have reported implementing flipped classroom curricula in the GME context, with inconclusive data on knowledge acquisition and retention and little data regarding feasibility . Furthermore, the impact of learning in the flipped classroom model on trainees’ clinical practice has not been studied and no prior studies have examined the use of the flipped classroom in internal medicine residency teaching sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Formative assessments included the prelesson exercises which were posted on the Vula discussion forum for all to comment, assess, and give feedback. These prelesson exercises aimed to facilitate the students to acquire key skills or understand concepts that the lesson was targeting to address as required for flipped classes (Riddell et al, 2017). Facilitators also used these preclass exercises to gauge general understanding of the concepts by the participants.…”
Section: Step 3: Goals and Specific Objectives For The Training Coursementioning
confidence: 99%